Research on the relationship between architectural features in northeast China and vertical aerosol transmission of COVID-19 - Li, Xia; Sun, Bingxin; Lyu, Keyang; Chen, Jiayu; Zhang, Yunjian; Sun, Yu; Li, Chenguang; Sui, Tianzhuo; Wang, Xinxin; Hu, Yu; Wang, Qin; Xu, Dongqun (Frontiers in Public Health, 2023)
During the COVID-19 pandemic, many buildings in northeast China have had clusters of infected cases in the vertical layout. There is speculation that vertical aerosol transmission occurs. The houses in northeast China are airtight, and range hoods may be used for a long period of time when cooking. The pathway and factors influencing vertical aerosol transmission are worth studying. To elucidate a viral aerosol transmission pathway, we selected a multistory apartment and a high-rise building in Changchun city, Jilin province, China, to conduct an in-depth investigation and on-site simulation experiments. According to epidemiological investigation information on infected cases, building structures, drainage, ventilation, etc., we used fluorescent microspheres to simulate the behaviors of infected people, such as breathing and flushing the toilet after defecation, to discharge simulated viruses and track and monitor them. The field simulation experiment confirmed the transmission of fluorescent microsphere aerosols to other rooms in two types of buildings using a vertical aerosol transmission pathway of toilet flush-sewage pipe-floor drain without a water seal. Our study showed that, in the absence of a U-shaped trap or floor drain water seal whether in a multistory apartment or high-rise residential building, there is a transmission pathway of “excretion of virus through feces-toilet flushing-sewage pipe-floor drain without water seal,” which will cause the vertical transmission of viral aerosol across floors during the COVID-19 pandemic. Moreover, the negative pressure generated by turning on the range hood when closing doors and windows increase aerosol transmission. Based on this negative pressure, prevention and control measures for residential buildings in northeast China during the COVID-19 pandemic were proposed.